(untitled) (Journal of Engineering, 2006)
The possibility of using inhibited hydrochloric acid in descaling of water deposits on heat exchanger and cooling system tubes have been investigated. A dynamic flow system was designed for this state. Experiments were carried out using different, temperatures, solution flow rates,times, and different hydrochloric acid concentrations inhibited with Hexamine. Kinetics of acid iron oxide scale reaction was studied using hydrochloric acid The kinetics analysis showed that the acid- FeO scale reaction followes 1st order reaction. It was found that the FeO scale removal was mass transfer controlling process. Iron- oxide scale removal process was analyzed as mass transfer operation and adequate semi- empirical correlations for scale removal (or mass transfer rate) under different conditions, in a dimensionless form have been obtained. The results of iron- oxide scale removal (or mass transfer rate) are compared with many proposed models particularly those based on the concept of analogy among momentum and mass transfer. Prandtl- Taylor analogy showed a good agreement with experimental mass transfer results.